Association between knowledge, attitude, practice and early childhood caries among parent-child dyad in Bangalore city: a cross sectional study - Lokesh, Yashas; P. Puranik, Manjunath; Rangarajurs, Sowmya K. (International Journal Of Community Medicine And Public Health, 2025)
Background: The knowledge, attitude and practice of parents have an impact on their children’s general and oral health. Hence this study was conducted to determine the association between knowledge, attitude, practices and early childhood caries among parent-child dyad. Methods: A cross sectional study was conducted among 432 parent-child dyad in Bangalore city. Children were selected from different government, private and aided schools across Bangalore city. A structured proforma was used to collect data regarding socio-demographic factors. Parental knowledge, attitude and practice regarding ECC were assessed using a pre-validated KAP questionnaire. Oral health was assessed using World Health Organization Oral Health Assessment Form for Children, 2013. Chi square test, Pearson’s correlation coefficient and multivariate linear regression analyses were performed and p<0.05 was considered statistically significant. Results: The mean age of the children was 4.0±0.82 years. Majority of the parents had fair knowledge (58%), positive attitude (61%) and good practice (38%). The prevalence of ECC experience among the study participants was 59.8%. The mean dmft was 3.10±3.73. There was a statistically significant association between parental knowledge, attitude, practices and early childhood caries (p<0.001). There was moderate negative correlation between parental KAP and ECC experience in children. Multivariate linear regression analyses revealed statistically significant association of knowledge, attitude and practices with ECC experience as a dependent variable (p<0.001). Conclusions: There was a significant association between parental knowledge, attitude and practice with ECC experience among preschool children. Hence, measures to improve parental KAP should be considered for better oral health outcomes in children.